Risk Factors for Zoonotic Tuberculosis at the Wildlife-Livestock-Human Interface in South Africa - Sichewo, Petronillah R; Michel, Anita L; Musoke, Jolly; Etter, Eric M C (MDPI AG, 2021)
A cross-sectional study was conducted to investigate the risk factors associated with zoonotic tuberculosis in humans and its transmission to people living at the wildlife-livestock-human interface. A questionnaire was administered to collect information on food consumption habits, food handling practices, and knowledge of zoonotic TB. Sputum samples were also collected from 150 individuals that belonged to households of cattle farmers with or without a bTB infected herd. In addition, 30 milk samples and 99 nasal swabs were randomly collected from cattle in bTB infected herds for isolation of Mycobacterium bovis (M. bovis). The sputum samples were screened for TB using the GeneXpert test and this was followed by mycobacterial culture and speciation using molecular techniques. No M. bovis was isolated from TB positive sputum samples and only one sample was confirmed as Mycobacterium tuberculosis (M. tuberculosis). M. bovis was isolated from 6.6% (n = 2/30) milk samples and 9% (n = 9/99) of nasal swabs. Ownership of a bTB infected herd and consumption of milk were recognized as highly significant risk factors associated with a history of TB in the household using multiple correspondence analysis (MCA) and logistic regression. The findings from this study have confirmed the potential for zoonotic TB transmission via both unpasteurized milk and aerosol thus, the role of M. bovis in human TB remains a concern for vulnerable communities.